1981
DOI: 10.1210/jcem-52-2-181
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination between Schizophrenic and Control Subjects by Means of Plasma Dehydroepiandrosterone Measurements

Abstract: In this study we were able to distinguish 10 schizophrenic subjects from 10 control subjects with 100% accuracy by measuring plasma dehydroepiandrosterone (DHEA) diurnal rhythms and analyzing the data using a linear function equation. Discrimination with this high level of accuracy is in contrast to most studies of altered biological functioning in schizophrenia which have yielded inconsistent results. These findings are regarded as preliminary; further study is necessary to elicit any consistent DHEA disturba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 8 publications
2
12
0
Order By: Relevance
“…More recent studies, arguably more accurate (due to improved methodological techniques), have reported elevated plasma levels of DHEA and DHEAS in severely psychotic male subjects (Howard, 1992), medicated patients with chronic schizophrenia (Oades and Schepker, 1994;di Michele et al, 2005) and in nonmedicated first-episode patients compared to controls. Abnormal plasma diurnal rhythms of DHEA, but not DHEAS, were observed in schizophrenia such that patients were distinguished from controls with 100% accuracy (Erb et al, 1981). It has been suggested that cortisol/DHEA or cortisol/DHEAS ratios may be more appropriate measures than DHEA or DHEAS alone (Hechter et al, 1997), and elevated ratios of cortisol/DHEA and cortisol/DHEAS have also been reported in schizophrenics compared to controls (Ritsner et al, 2004).…”
Section: Neuroactive Steroids In Schizophreniamentioning
confidence: 99%
“…More recent studies, arguably more accurate (due to improved methodological techniques), have reported elevated plasma levels of DHEA and DHEAS in severely psychotic male subjects (Howard, 1992), medicated patients with chronic schizophrenia (Oades and Schepker, 1994;di Michele et al, 2005) and in nonmedicated first-episode patients compared to controls. Abnormal plasma diurnal rhythms of DHEA, but not DHEAS, were observed in schizophrenia such that patients were distinguished from controls with 100% accuracy (Erb et al, 1981). It has been suggested that cortisol/DHEA or cortisol/DHEAS ratios may be more appropriate measures than DHEA or DHEAS alone (Hechter et al, 1997), and elevated ratios of cortisol/DHEA and cortisol/DHEAS have also been reported in schizophrenics compared to controls (Ritsner et al, 2004).…”
Section: Neuroactive Steroids In Schizophreniamentioning
confidence: 99%
“…Previous studies investigating DHEA blood levels in concentrations in psychosis or schizophrenia have demonstrated low DHEA levels (Tourney and Hatfield, 1972;Oertel et al, 1974;Harris et al, 2001) observed by some particularly in the morning (Tourney and Erb, 1979), abnormal DHEA diurnal rhythms (Erb et al, 1981), and no differences in DHEA levels (Brophy et al, 1983;Ritsner et al, 2004) compared to matched healthy controls. DHEAS levels have been reported to possibly be elevated (Oades and Schepker, 1994;Strous et al, 2004) and no different (Ritsner et al, 2004) in schizophrenia patients compared to healthy controls.…”
Section: Introductionmentioning
confidence: 98%
“…As to the circadian rhythm of cortisol, it has been more frequently investigated [Franzen, 1971;Adadevoh and Asuni, 1973;Erb et al, 1981], but with very incon sistent results.…”
Section: Introductionmentioning
confidence: 99%